Safety Behaviour Tendency Among Welders By Utilising Personal Protective Equipment - Rizky Maharja; Jihan Faradisha; Andi Mifta Farid Panggeleng (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Welding is one type of work potentially triggering work accidents. It is thus necessary to prevent work accidents in welding to minimize potential hazards and to prevent both work accidents and significant losses by the safety behaviour by using personal protective equipment. This current study aims to analyze the tendency of safety behaviour among welders in using PPE properly. This research was conducted through an analytic observational study using a cross-sectional design. It was carried out on welders at one of the shipbuilding companies in Indonesia. Sampling was chosen using a total population of 58 respondents. All research instruments, questionnaires, and analysis sheets have been tested for validity and reliability. The researchers looked at the Odds Ratio in the Ordinal Regression test to see behaviour tendency. The results suggest that the variables of knowledge, OSH training, and the reward system have a value of OR > 1. the variables of attitude, work readiness, availability of PPE, OSH promotion, and interaction between workers have a value of OR <1. This study found that welders tend to perform good safety behaviour using personal protective equipment based on determinants of behaviour such as knowledge, attitude, work readiness, availability of PPE, the interaction between workers, OSH promotion, OSH training, reward system, and supervision. Nevertheless, based on the OR value, the safety behaviour tendency differs for each behavioural determinant.